Obligation to adopt a resolution declaring the expiry of a councilor’s mandate in light of administrative court case law (Discourse of Law and Administration, 2026)
The study presents selected issues related to the obligation of the legislative body of a local government unit to adopt a resolution stating the expiry of the mandate of a councillor of that unit. It was emphasized, the mandate of a councillor expires by operation of law, but the legislative body must confirm this fact by resolution so that it produces legal effects. The specificity of adopting the resolutions in question is that the council is authorized to assess whether there is a material premise for the expiry of the mandate. For example, whether the councillor has violated the statutory prohibition of combining the mandate of a councillor with the performance of functions or activities specified in separate regulations. However, if the council determines that there is a material premise for the expiry of the mandate, it is obliged to adopt a resolution confirming the expiry of the mandate – in this sense, the council has no freedom. A resolution must be adopted in an appropriate manner and neither the council nor the councillor himself is entitled to “block” its adoption and cause the mandate to be held by a person who violates the prohibitions and restrictions established by the legislator.